The Influence of Sundanese Cultural Values on State Civil Apparatus at the Education Office of West Java Province - Prima Setiawan; Asep Hendra (Jurnal Media Birokrasi, 2025)
Culture is one of the concepts of local wisdom that necessity to be maintained. Sundanese culture is a culture that comes from the Sundanese people. The word "Sunda" means Good, White, Clean, and Brilliant, everything that contains elements of goodness. Sundanese people are believed to have Kasundaan ethos, character, and the virtues of life. The relationship between humans and fellow human beings in Sundanese society must be based on the attitude of "silih asah, silih asuh, and silih asih", meaning that they must teach each other, nurture each other, and love each other to create an atmosphere of community life that is colored by intimacy, harmony, peace, tranquility, and kinship. The creation of a good culture improves performance in an organization. The purpose of this study is to analyze the influence of Sundanese cultural values on the performance of State Civil employees at the West Java Provincial Education. Quantitative research is the method used in this study. A total sample of 395 workers was gathered by employing stratified cluster random sampling. Structural Equation Modeling (SEM) analysis utilizing AMOS 22.0 software is the study methodology used. The findings of this study show that Sundanese cultural values significantly affect performance by 14.0%, (p<0.05). Keywords: performance, Sundanese Cultural Values.